Identifying of Anti-Thrombin Active Components From Curcumae Rhizoma by Affinity-Ultrafiltration Coupled With UPLC-Q-Exactive Orbitrap/MS - Zhenwei Lan; Ying Zhang; Yue Sun; Lvhong Wang; Yuting Huang; Hui Cao; Shumei Wang; Jiang Meng (Frontiers Media S.A., 2021)
Recent studies concerning products that originate from natural plants have sought to clarify active ingredients, which both explains the mechanisms of the function and aids in quality control during production. As a traditional functional plant, Curcumae Rhizoma (CR) has been proven to be effective in promoting blood circulation and removing blood stasis. However, the components that play a role in its huge compound library are still unclear. The present study aimed to develop a high-throughput screening method to identify thrombin inhibitors in CR and validate them by in vitro and in vivo experiments. The effect of CR on thrombin in HUVECs cells was determined by ELISA, then an affinity-ultrafiltration-UPLC-Q-Exactive Orbitrap/MS approach was applied. Agatroban and adenosine were used as positive and negative drugs respectively to verify the reliability of the established method. The in vitro activity of the compounds was determined by specific substrate S-2238. The in vivo effect of the active ingredients was determined using zebrafish. Molecular docking was used to understand the internal interactions between compounds and enzymes. ELISA results showed that CR had an inhibitory effect on thrombin. The screening method established in this paper is reliable, by which a total of 15 active compounds were successfully identified. This study is the first to report that C7, 8, and 11 have in vitro thrombin-inhibitory activity and significantly inhibit thrombosis in zebrafish models at a safe dose. Molecular docking studies were employed to analyze the possible active binding sites, with the results suggesting that compound 16 is likely a better thrombin inhibitor compared with the other compounds. Based on the affinity-ultrafiltration-UPLC-Q-Exactive Orbitrap/MS approach, a precisely targeted therapy method using bio-active compounds from CR might be successfully established, which also provides a valuable reference for targeted therapy, mechanism exploration, and the quality control of traditional herbal medicine.